A Computational and Graphical Approach to Analyze the Dynamic Wavelet Correlation among Components of a Nonlinear Dynamical System - Polanco-Martínez, Josué M. (Journal of Applied Nonlinear Dynamics, 2026)
An innumerable number of phenomena that take place in nature can be represented as dynamical systems, which in many cases are not linear. One of the common tasks performed in the study of these systems is to analyse through time and frequency the relationships among their components. In this work, we present, discuss, and extend for the first time in the study of nonlinear dynamical systems, a mathematical and computational tool, the wavelet local multiple correlation (WLMC) to analyse quantitatively and visually the behaviour among components of nonlinear dynamical system. The Lorenz system is used as a case study. The WLMC analysis presented shows that the WLMC is able to capture the most relevant periodic and chaotic dynamics of the Lorenz system as well as the "dominant" components of this dynamical system. These results confirm that the WLMC is an adequate mathematical tool to analyse nonlinear and chaotic dynamical systems with multiple components.